2019
DOI: 10.31234/osf.io/pfz2g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Fan Effect for Creative Thought: Semantic Richness Facilitates Idea Quantity but Constrains Idea Quality

Abstract: Creative thinking has long been associated with spreading of activation through concepts within semantic memory. Despite its theoretical importance, little is yet known about how semantic memory structure facilitates and constrains idea production. We examine one potential influence on spreading activation during divergent thinking known as the fan effect: increasing knowledge about a concept leads to increasing interference from conceptually related information. Specifically, we tested whether cue association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…On the other hand, a combination of low CC, high ASPL, and high Q is characteristic for sparse connectivity network structure that constrains the spreading of activation among concepts and/or semantic clusters (i.e., yields less efficient propagation of information), thus alleviating the load on controlled inhibitory processing imposed by multiple and strongly interconnected associates. In support of this notion, increased number of associates to a concept has recently been considered a source of semantic interference imposing an increased need for cognitive control, especially when the typical/dominant responses are to be suppressed (Beaty et al, 2019). Taken together, these findings indicate that the structural properties of semantic representation may parametrically modulate the engagement of various (controlled) processes supporting semantic memory retrieval, and thus affect higher-level cognition.…”
mentioning
confidence: 86%
“…On the other hand, a combination of low CC, high ASPL, and high Q is characteristic for sparse connectivity network structure that constrains the spreading of activation among concepts and/or semantic clusters (i.e., yields less efficient propagation of information), thus alleviating the load on controlled inhibitory processing imposed by multiple and strongly interconnected associates. In support of this notion, increased number of associates to a concept has recently been considered a source of semantic interference imposing an increased need for cognitive control, especially when the typical/dominant responses are to be suppressed (Beaty et al, 2019). Taken together, these findings indicate that the structural properties of semantic representation may parametrically modulate the engagement of various (controlled) processes supporting semantic memory retrieval, and thus affect higher-level cognition.…”
mentioning
confidence: 86%
“…Dumas & Dunbar, 2014). Recent work suggests that this low inter-item correlation could be due to variability in item (object) characteristics such as semantic object features (Beaty, Kenett, Hass, & Schacter, 2019) and word frequency (Forthmann et al, 2016). At the same time, low inter-task fluency correlations have not been consistently reported in the literature; for example reported high standardized factor loadings on an AUT fluency latent variable (suggesting strong reliability) and reported inter-task correlations for AUT items ranging from .57 to .71.…”
Section: Measuring Creativity: the Status Quomentioning
confidence: 99%
“…Dumas & Dunbar, 2014). Recent work suggests that this low inter-item correlation could be due to variability in item (object) characteristics such as semantic object features (Beaty, Kenett, Hass, & Schacter, 2019) and word frequency (Forthmann et al, 2016). At the same time, low inter-task fluency correlations have not been consistently reported in the literature; for example, Jauk et al (2014) reported high standardized factor loadings on an AUT fluency latent variable (suggesting strong reliability) and reported inter-task correlations for AUT items ranging from .57 to .71.…”
Section: Measuring Creativity: the Status Quomentioning
confidence: 99%